Quantification and bioremediation of landfill methane / Siva Shangari a/p Govindan - Govindan, Siva Shangari (2014)
Methane (CH4) a potent greenhouse gas (GHG), has more than doubled in past decades and continues to rise. Historically, landfills have been the largest source of anthropogenic CH4 emission from the waste sector with 6,875 million metric tonnes of CO2–eq in year 2010. Therefore, it is important to quantify CH4 emissions from landfills to evaluate measures for reduction of GHG emission which contributes to global warming and climate change. At present, CH4 emission rates from landfills have been estimated using mathematical and empirical models and among them, the first-order-decay (FOD) models are often credited for its estimation. The objective of this study is to quantify the CH4 emission from Jeram Sanitary Landfill (JSL) in Kuala Selangor using the IPCC Waste Model. The output was verified using error function analysis (EFA) and later was used to calculate CH4 emission from a temporarily closed cell. Quantification of CH4 surface emission was also estimated using the flux chamber technique. Next, the influence of meteorological parameters such as rainfall, temperature, humidity and atmospheric pressure on CH4 surface emission from landfill was also studied. As a part of the climate change mitigation effort, two cover materials to enhance CH4 oxidation were designed for JSL using organic waste; (1) from a mixture of brewery spent grain (BSG) and compost of grass and cow manure; (2) BSG which was made into compost. Batch experiments were conducted to determine the ratio of BSG to compost, amount of material and optimum parameters for pH, moisture content and temperature. Column experiment to determine the best height/thickness of the biocover material was conducted subsequently. From the model verification exercise, it was noted that the IPCC Waste Model overestimated CH4 emission at JSL by 7% to 60%. The model input values which showed the least deviation from EFA was used as the site specific value for JSL. In terms of the meteorological parameters, only rainfall had a strong positive linear correlation to the surface emission of CH4 during the wet period. As for the biocover performance, BSG and compost mixture was better at oxidizing CH4 than the composted BSG. The 7:3 ratio of BSG to compost mixture with pH 6, 65% moisture and temperature at 35°C had the highest CH4 oxidation in the batch experiment. In terms of the column experiment with laboratory condition, complete CH4 oxidation was the fastest at 50cm height (within 5 days). While in the landfill, complete CH4 oxidation was the fastest at 60cm height and it took 6 days to achieve it. On the other hand, BSG compost did not show good CH4 oxidation potential. In conclusion, the two methods used to quantify CH4 emission at JSL was a complement of each other. The influence of rainfall on the CH4 flux emission was significant. Besides that, the use of BSG and compost mix as a biocover material had enhanced CH4 oxidation through microbial activity thus reducing the CH4 emission to the atmosphere.